Diversity in Everyday Discourse: The Cultural Ambiguities and Consequences of “Happy Talk” - Bell, Joyce M.; Hartmann, Douglas (American Sociological Review, 2007)
Few words in the current American lexicon are as ubiquitous and ostensibly uplifting as diversity. The actual meanings and functions of the term, however, are difficult to pinpoint. In this article we use in-depth interviews conducted in four major metropolitan areas to explore popular conceptions of diversity. Although most Americans respond positively at first, our interviews reveal that their actual understandings are undeveloped and often contradictory. We highlight tensions between idealized conceptions and complicated realities of difference in social life, as well as the challenge of balancing group-based commitments against traditional individualist values. Respondents, we find, define diversity in abstract, universal terms even though most of their concrete references and experiences involve interactions with racial others. Even the most articulate and politically engaged respondents find it difficult to talk about inequality in the context of a conversation focused on diversity. Informed by critical theory, we situate these findings in the context of unseen privileges and normative presumptions of whiteness in mainstream U.S. culture. We use these findings and interpretations to elaborate on theories of the intersection of racism and colorblindness in the new millennium.